2004
DOI: 10.1023/b:clin.0000046134.80393.34
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate reduces liver metastasis of rat colon carcinoma cells in vivo and resistance to oxidative stress in vitro

Abstract: Injection of the rat colon carcinoma cell line CC531 into spleen of syngeneic rats results in considerable amounts of liver metastases within 14 days. We investigated whether preincubation of the cells with butyrate reduced their metastatic ability in vivo and whether this was accompanied by reduction in related properties such as secretion of metalloproteinases and their ability to withstand oxidative stress. Butyrate incubation reduced cell growth rate and initiated apoptosis in a dose- and time-related mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
1
12
0
3
Order By: Relevance
“…These findings indicated that GSH depletion might be one of the mechanisms underlying butyrate-induced cytotoxicity. Our results were in agreement with Li et al (27) who reported that treatment of butyrate in colon cancer cells reduces the cellular GSH levels. Recently, exposure of butyrate can deplete GSH in MCF-7 breast cancer cells (28).…”
Section: Discussionsupporting
confidence: 94%
“…These findings indicated that GSH depletion might be one of the mechanisms underlying butyrate-induced cytotoxicity. Our results were in agreement with Li et al (27) who reported that treatment of butyrate in colon cancer cells reduces the cellular GSH levels. Recently, exposure of butyrate can deplete GSH in MCF-7 breast cancer cells (28).…”
Section: Discussionsupporting
confidence: 94%
“…The use of CC531 colon carcinoma cells in tumor metastasis models has been evaluated in several studies [19][20][21][22][23][24]. It has been shown that CC531 cells injected into the vena mesocolica are a reliable tumor metastasis model.…”
Section: Discussionmentioning
confidence: 99%
“…Although butyrate serves as a source of oxidative fuel for normal colonocytes, addition of it to neoplastic cells inhibits hyperproliferation and drives terminal differentiation and/or apoptosis [16 -18]. Consistent with its anticarcinogenic role in vitro, increased butyrate production is closely correlated with the reduction of tumor mass in animal models [35,36]. Although several studies have revealed that NaBT can induce apoptosis [37 -39], we suppose that NaBT-induced cell differentiation or apoptosis depends on its dosage.…”
Section: Discussionmentioning
confidence: 99%